(untitled) (TEL Tempo, Espaço e Linguagem, 2024)
This article focuses on the life, training, work and professional development trajectories of a history teacher, with the aim of understanding and analyzing these paths, considering the various nuances of the theoretical-methodological lenses of the (self) biographical approach in the educational field and in the constitution of teacher training and research. To this end, the article has undertaken a discussion of specialized literature to support proposals for possible understandings of teacher narratives, as well as presenting excerpts from teacher narratives. The text has thus gone through a process of recognizing the teacher’s experiences, memories and subjectivities in interface with the collective aspects of the social world, drawing attention to the proposition of possible further research. Keywords: (Self) biographical research. Teacher training. Professional development.